Application for Data Processing of KKNT Student Activities in Sei Limbat Village, Selesai District, Langkat Regency - Hafni, Hafni; Zen, Muhammad; Syahpita Tarigan, Junusdad (Bahasa Indonesia, 2024)
Thematic Real Work Lecture (KKNT) is a form of education by providing learning experiences for students to live in the community outside the campus, who are directly together with the community to identify potential and handle problems so that they are expected to be able to develop the potential of the village / region and concoct problems in the village. KKNT activities are expected to hone partnership soft skills, interdisciplinary / scientific teamwork (cross-competency), and student leadership in managing development programs in rural areas. The purpose of KKNT activities is an activity to provide opportunities for students to apply their knowledge, technology and skills to collaborate with many stakeholders in the field, and help accelerate development in rural areas. The results of this service will record the activities of KKNT students in this application, from each KKNT student activity from the results of monitoring by field supervisory lecturers that the KKNT students 90% carry out activities with partner field supervisors and 10% of making KKNT student activity reports.